PENCEGAHAN STUNTING MELALUI PENYULUHAN PRANIKAH PADA CALON PENGANTIN: PENCEGAHAN STUNTING MELALUI PENYULUHAN PRANIKAH PADA CALON PENGANTIN - Maulidar Marzuki; Fera Rizka; Hasratina Hasratina; Manisa Salaila; Izzatul Muna; Khairun Nisak; Dewi Maritalia (LPPM Universitas Al Muslim, 2022)
Stunting is a problem in the growth and development of children which will have an impact on the quality of human resources in the future. Prevention of stunting needs to be done as early as possible to prevent the increasing number of stunting incidents in Indonesia, especially in Bireuen Regency which is one of the loci for stunting. Various efforts have been made to reduce and prevent stunting, including by providing premarital counseling to prospective brides and grooms, as was done by lecturers and students of the Diploma III Midwifery Program at Almuslim University. Prevention of stunting through premarital counseling in Kota Juang District, Bireuen Regency is carried out considering that stunting prevention is effective in the First 1000 Days of Life (HPK). The media used in this extension are infocus, leaflets and banners. The participants who were the bride and groom were very enthusiastic about participating in the counseling which lasted for approximately two hours, as seen from the number of questions asked during the question and answer session. The KUA officers of Kota Juang district were very supportive of the community service activities carried out by the lecturers and students of Diploma III Midwifery at Almuslim University and it was hoped that in the future this kind of collaboration will continue with different counseling topics and are much needed by the bride and groom who are also prospective parents for their sons. their future daughter.